PEMBELAJARAN MENULIS TEKS DRAMA MENGGUNAKAN MODEL EXAMPLE NON EXAMPLE BERBANTUAN MEDIA GAMBAR KARIKATUR - ramlah, Ramlah; Wikanengsih, Wikanengsih; Fauziya, Diena San (IKIP Siliwangi, 2020)
This research is motivated by the importance of learning drama texts in schools. The drama text is a story of human conflict in the form of dialogue that is expressed using conversation. The formulation of the problem of this research are 1) How is the scenario and implementation of learning to write drama texts in class VIII students using the example non example model assisted by caricature drawing media; 2) how the responses of teachers and students of class VIII by using a model example non example assisted by caricature drawing media; 3) what difficulties experienced by students of class VIII in completing the tasks of writing drama texts. The purpose of this research is to describe the three problem formulations. Researchers use descriptive qualitative methods that are methods with the aim of describing, explaining, and analyzing the problems contained in a study. The results obtained are changes between the scenario and implementation. But learning goes well, this is evidenced by the results of observations with a value of 81.57, meaning that it is classified as very good. Likewise the teacher's response with a percentage of 96.87% means that it is classified as very good. While the percentage of student responses of 81.87% means that it is classified as good. The test results obtained by students namely an average number of 79.38 have met the indicators of success. Then, for the difficulties experienced by students can be seen from the matter of knowledge about the analysis of dialogue in fragments of drama and about the skills of writing the rules of drama language.